A comparative exploration of celebrity chef influence on millennials. Issue 5 (2nd September 2020) - Cifelli, Briana; Kurp (Maher), Jill; Clarke, Theresa B.; Clarke, Irvine
ABSTRACT: This study extends literature about celebrity chef influence and millennial food habits. It explored the impact of chefs' engagement in Corporate Social Responsibility (CSR) efforts. Data was collected from over 245 involved millennials through an online Qualtrics survey. Results illustrated that millennials are not all the same. Significant differences were found in millennials' motivations for watching celebrity chefs, the influence of chefs on food habits, and awareness of the chefs' CSR initiatives based on involvement. Millennial awareness of chef CSR activities is related to chef influence. This study extended understanding of celebrity chef influence on millennials' by taking different levels of involvement into account and expanding knowledge about motives for celebrity chef engagement. Since millennials differed based on levels of involvement, findings have implications for various types of chef engagement with this generation. Implications are presented for chefs' CSR activities at the local/regional levels since chefs are often asked to donate resources in their communities. An original contribution of this work is the Celebrity CSR Engagement Classification where four categories emerged based on different celebrity chef influences on food habits: Founders, Supporters, Powerhouses, and Laggards . The classification may be adapted for CSR research about other celebrities besides chefs.